Uloga dispozicijskih, socijalizacijskih i ponašajnih čimbenika u dinamici slanja seksualno eksplicitnih poruka u adolescenciji - Burić, Jakov (Array, 2018)
The research suggests that a significant number of adolescents is using sexually explicit material (SEM). Simultaneously, the rapid development of mobile technologies and online social networks led to a new type of sexualized behaviour – sexting. Current research pointed to the relationship between SEM use, sexting, and risky sexual behaviour. Considering Differential Susceptibility to Media Effects Model (DSMM; Peter & Valkenburg, 2013), the aim of this longitudinal research was to assess the contribution of type of high school, parental education, parental monitoring, sensation seeking, self-esteem, anxiety and depression, religiosity, sexual initiation, SEM use, and online social network use in explaining sexting among adolescents. The research was conducted on a population sample of 791 high school students in Rijeka (302 boys and 489 girls) with a mean age of 15.8 years (SD = 0.51). The data were collected at two time points with 12 months difference. Out of a total number of respondents, 46% boys in first and 37.7% in the second wave reported sexting at least once, while 36.6% of girls in first and 33.7% in second wave reported the sexting at least once. Considering the differences in adolescents' sexual socialization, all analyses were done separately for boys and girls. The results of the multivariate analysis (we used hierarchical regression analysis while controlling the outcome initial values) revealed that girls higher on sensation seeking, sexually active girls, and the ones using SEM more often at wave 1 were more likely to sext in wave 2. In a sample of boys, only sensation seeking emerged as a positive predictor of sexting at wave 2. Considering the enormous popularity of online networks, these results point to the importance of media literacy education as well to better understanding the characteristics of adolescents engaging in sexting.